The temporality of economic decisions applied to clinical reasoning - João Victor Almeida dos Santos; Luís Cláudio Lemos Correia (Journal of Evidence-Based Healthcare)
INTRODUCTION: Medical thinking lacks economic thinking although temporality plays a crucial role in shared clinical decision-making. Present benefits, such as symptom relief, at times, should not be underestimated in the economic evaluation of medical interventions; and immediate effects in present benefit scenarios allow for valuable feedback, aiding in the assessment of the appropriateness of the chosen intervention. Ultimately, we underscore the need for a nuanced understanding of the interplay between time, costs, and benefits in clinical decision-making.